Experimental evaluation of the thermal and exergy performance of a flat spiral-tube receiver for a parabolic dish collector - Ahmad Yonanda; Muhammad Raihan Junidy; Muhammad Irsyad; Amrizal Amrizal; Harmen Harmen; Dondi Kurniawan; Angga Darma Prabowo (Jurnal Polimesin, 2025)
Global dependence on fossil fuels continues to drive the search for cleaner, more sustainable energy sources. One promising technology is the Parabolic Dish Collector (PDC), harnessing concentrated solar energy. The receiver in a PDC is pivotal to overall thermal efficiency and useful energy output. This study evaluates the thermal and exergy performance of a manufactured flat spiral-tube receiver designed to enhance heat transfer. Experiments were conducted under tropical condition between 10:00 and 14:00 local time at three volumetric flow rates (0.5, 0.8, and 1.1 LPM). The 0.5 LPM flow rate yielded the best performance, with a fluid temperature rise up to 43.8Â°C, a thermal efficiency of 39.1%, and a peak exergy efficiency of 1.1%. The spiral geometry improved fluid residence time, enabling more effective heat absorption. These findings demonstrate that a simple, manufactured spiral tube receiver can improve PDC performance, offering an efficient and cost-effective solution for solar thermal systems.